CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI INSTRUMEN HUKUM EKONOMI DI ERA GLOBALISASI - Nur Sulistyo B. Ambarini (Jurnal Dinamika Hukum, 2010)
Globalization of the world have substantial influence the development of the state and the country of Indonesia. One of the globalization trends that influence the development of economic law in Indonesia is the Corporate Social Responsibility (CSR). Corporate Social Responsibility (CSR) is a concept in economic activity associated with the embodiment of the concept of Sustainable Development . CSR arrangements in legislation, are a reflection of the principle of government intervention. In this regard CSR as an instrument of economic laws is mandatory to become a tool for corporate or business entity for achieve sustainable development and environmentally sound. This is intended as an effort to provide protection to the community, environment and natural resources of the business practices that harm. In addition it also guarantees the performance of firms in the economy in a balanced way to achieve socio-economic  welfare of society. Keywords:         Corporate Social Responsibility (CSR); Economic Law, Globalization.